TOPOEKPHRASIS IN THE SHORT STORY «DON'T LOOK NOW» BY DAPHNE DU MAURIER (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-129-140The topoekphrasis in D. du Maurier's short story «Don't Look Now» has been investigated. Under the term ‘Topoekphrasis’ we mean a description of the scene of action, which "is the hero of a literary work" (O. Kling) and has a special aesthetic significance. Such a place in the analyzed novel is Venice, which, thanks to its unique architectural appearance, has become a true work of art. The image is created by a description of the world-famous architectural monuments of Venice, as well as the use of toponyms reflecting the features of the urban landscape. Speaking about real-life art objects, the author does not strive for an accurate description of his visual image but fills it with additional meaning. The text of the novel demonstrates various types of ekphrastic descriptions. Their usage depends on the purpose, the amount of necessary visual information and the specifics of the art object described. The absence of detailed descriptions determines the use of zero and paratactic variants of topoekphrasis, the emphasis on the state of the characters, on the perception and interpretation of the visual image and the development of the action indicates its interpretive nature. The role of mortal motifs and labyrinth in the formation of topoekphrasis is noted. We have also knotted that the novel by D. du Maurier fits into the context of the world Venetian, expanding its semantic field.Key words: topoekphrasis, art object, Venice, visualization, labyrinth, toponym, landscape, gondola, church, Grand Canal